2020
DOI: 10.1139/cjfas-2019-0317
|View full text |Cite
|
Sign up to set email alerts
|

Abiotic conditions are unlikely to mediate hybridization between invasive rainbow trout and native Yellowstone cutthroat trout in a high-elevation metapopulation

Abstract: Understanding factors mediating hybridization between native and invasive species is crucial for conservation. We assessed the spatial distribution of hybridization between invasive rainbow trout (Oncorhynchus mykiss) and native Yellowstone cutthroat trout (Oncorhynchus clarkii bouveri) in the Lamar River of Yellowstone National Park using a paired telemetry and genetic dataset. Spawning populations containing hybrids (15/30) occupied the full spectrum of abiotic conditions in the watershed (stream temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 60 publications
1
4
0
Order By: Relevance
“…Studies that identified non-backcrossed later generation hybrids only found relatively low numbers of F2 individuals (Bennett & Kershner, 2009;Gunnell et al, 2008;Young et al, 2001). A notable exception is Heim et al (2020) trout, Yellowstone cutthroat trout and hybrid juveniles in a laboratory setting revealed no higher incidence of phenotypic abnormalities in F2 juveniles relative to the unadmixed parental species (Ostberg et al, 2011); in conjunction with our observation of F2 juveniles, these results suggest that selection against F2+ hybrid individuals is occurring at a later life stage. Selection against hybrids in later life stages has also been observed in Populus hybrids (Lindtke et al, 2014).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Studies that identified non-backcrossed later generation hybrids only found relatively low numbers of F2 individuals (Bennett & Kershner, 2009;Gunnell et al, 2008;Young et al, 2001). A notable exception is Heim et al (2020) trout, Yellowstone cutthroat trout and hybrid juveniles in a laboratory setting revealed no higher incidence of phenotypic abnormalities in F2 juveniles relative to the unadmixed parental species (Ostberg et al, 2011); in conjunction with our observation of F2 juveniles, these results suggest that selection against F2+ hybrid individuals is occurring at a later life stage. Selection against hybrids in later life stages has also been observed in Populus hybrids (Lindtke et al, 2014).…”
Section: Discussionsupporting
confidence: 76%
“…Studies that identified non‐backcrossed later generation hybrids only found relatively low numbers of F2 individuals (Bennett & Kershner, 2009; Gunnell et al, 2008; Young et al, 2001). A notable exception is Heim et al (2020), which identified higher numbers of intermediate, non‐F1 hybrids, though F3 individuals were still not identified and the assignment of traditional hybrid classes (F1, F2, etc.) was complicated by the general lack of unadmixed rainbow trout individuals in the system.…”
Section: Discussionmentioning
confidence: 99%
“…This can be advantageous as compared to complete eradication with chemical treatments and re-stocking native trout, because the local adaptations of the native population can be conserved. However, a long history of failed attempts to control invasive salmonids has shown that capturing sufficient numbers of fish to effect a biological change requires substantial effort, particularly in large streams (Hansen et al 2019). Because YCT, RT, and their hybrids are highly regarded sport fish (Quist and Hubert 2004), leveraging public harvest could be a useful strategy to supplement removal efforts by management agencies (Flinders et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…2019; Heim et al. 2020). Invasive piscivores are especially harmful because they often add a novel predatory trophic level, resulting in trophic cascades that alter the structure of aquatic and terrestrial food webs (Ellis et al.…”
mentioning
confidence: 99%
“…Invasive fish have caused ecological and economic damage worldwide by altering aquatic communities and disrupting natural ecosystem processes (Leprieur et al 2008;Gallardo et al 2016;Cuthbert et al 2021). Invasive fish are particularly detrimental (O'Gorman et al 2021) in the western United States, where fish species richness is naturally low, causing declines in native and popular wild sport fish populations through predation (Ruzycki 2004;Loppnow et al 2013;Sepulveda et al 2013), competition (Donald and Alger 1993;Roth et al 2020;Wainright et al 2021), and hybridization (Kovach et al 2011;Mandeville et al 2019;Heim et al 2020). Invasive piscivores are especially harmful because they often add a novel predatory trophic level, resulting in trophic cascades that alter the structure of aquatic and terrestrial food webs (Ellis et al 2011;Koel et al 2019;Wainright et al 2021).…”
mentioning
confidence: 99%